Creating virtual 3‐dimensional models for teaching pre‐clinical tooth preparation: Students' usages and perceptions. (17th April 2018) - Lin, W. S.; Chou, J. C.; Charette, J. R.; Metz, M. J.; Harris, B. T.; Choi, N.
Abstract: Purpose: This research aimed to evaluate the students' usage and perceptions of using smartphones in their general dental education and learning tooth preparation with the individually designed virtual 3D instructional models in the pre‐clinical removable partial denture course. Materials and Methods: Second‐year dental students were asked to voluntarily participate in a survey to investigate their demographic information, general usages of smartphones, perception of smartphones usage in dental education (construct 1) and perception of individually designed virtual 3D instructional models (construct 2). Students' responses of general usages of the smartphones were compared with their demographic and educational backgrounds using nonparametric Kruskal‐Wallis test (for age) and Fisher's exact test (for sex, race and educational background). The sums of scores of the construct 1 and construct 2 were tested for associations with student's demographic and educational backgrounds using the Pearson product‐moment correlation (for age), t test (for sex and educational background) or one‐way ANOVA F test (for race) (α = .05). Results: A 75% response rate (N = 90) was achieved in this study, and all 90 participants owned smartphones. Students' responses to general usages of the smartphones were not significantly influenced by their demographic background. For the construct 1, more than 73% of participants responded either agree or strongly agree to the usage of smartphones in general dental education and pre‐clinical setting; however, only 49% of participants responded the same way in the clinical setting. For the construct 2, 48 of 90 participants viewed the 3D models, and more than 73% of these 48 participants responded either agree or strongly agree to the usage of the 3D models in the pre‐clinical course. Student's demographic background did not have significant influence on the sums of scores of the construct 1 and construct 2. Conclusions: Within the limitations of this study, high usages and ownerships of smartphones were found amongst the students surveyed. The individually designed virtual 3D instructional models as supplemental teaching materials in the pre‐clinical course were perceived positively by the students.